Effectiveness of interventions to prevent perinatal depression: An umbrella review of systematic reviews and meta-analysis - Motrico, Emma; Bina, Rena; Kassianos, Angelos P.; Le, Huynh-Nhu; Mateus, Vera; Oztekin, Deniz; Rodriguez-Muñoz, Maria F; Moreno-Peral, Patricia; Conejo-Cerón, Sonia (My University, 2023)
To date, dozens of systematic reviews (SRs) and meta-analyses (MAs) summarize the effectiveness of preventive interventions for perinatal depression. However, the results are inconclusive, making an urgent need to step up to higher levels of evidence synthesis.
Keywords: depression; meta-analysis; Perinatal; Prevention; Randomized control trial; systematic review